Stress hyperglycemia as a modifiable predictor of futile recanalization in patients undergoing mechanical thrombectomy for acute ischemic stroke - Merlino, Giovanni; Pez, Sara; Sartor, Roberto; Kuris, Fedra; Tereshko, Yan; Nesi, Lorenzo; Lorenzut, Simone; Janes, Francesco; Sponza, Massimo; Gavrilovic, Vladimir; Marotti, Nicola; Pellegrin, Andrea; et al. (Frontiers in Neurology, 2023)
Introduction Mechanical thrombectomy (MT) is the first line treatment in acute ischemic stroke (AIS) due to large vessel occlusion (LVO). Approximately half of patients treated with MT does not have a favorable outcome 3 months after stroke. The aim of this study was to identify predictors of futile recanalization (FR) in patients with LVO treated with MT. Methods A retrospective analysis of consecutive patients with acute ischemic stroke due to anterior circulation LVO who underwent MT. Patients with a TICI score of 2b or 3 were included. We distinguished two groups, FR and meaningful recanalization (MR), according to patients' disability three months after stroke (FR: mRS score > 2; MR: mRS score < 2). Results We enrolled 238 patients (FR, n = 129, 54.2%; MR, n = 109, 45.8%). Age (OR 1.05, 95% CI 1.01–1.09, p = 0.012), female sex (OR 2.43, 95% CI 1.12–5.30, p = 0.025), stress hyperglycemia, as measured by the GAR index, (OR 1.17, 95% CI 1.06–1.29, p = 0.002), NIHSS at admission (OR 1.15, 95% CI 1.07–1.25, p = 0.001) and time from symptoms onset to MT (OR 1.01, 95% CI 1.00–1.01, p = 0.020) were independent predictors of FR. The AUC for the model combining age, female sex, GAR index, NIHSS at admission and time from symptoms onset to MT was 0.81 (95% CI 0.76–0.87; p < 0.001). The optimal GAR index cut-off score to predict FR was 17.9. Discussion FR is common after MT. We recognized older age, female sex and baseline NIHSS as non-modifiable predictors of FR. On the other hand, time from symptoms onset to MT and stress hyperglycemia were modifiable pre- and post-MT factors, respectively. Any effort should be encouraged to reduce the impact of these modifiable predictors.